Apples and dragon fruits: the determinants of aid and other forms of state financing from China to Africa - Dreher, Axel; Fuchs, Andreas (International studies quarterly, 2018)
Abstract. Chinese “aid” is a lightning rod for criticism. Policy-makers, journalists, and public intellectuals claim that Beijing uses its largesse to cement a
Gesehen am 14.06.2019